Pengaruh Teknik Mencatat Mind Mapping pada Model Pembelajaran Learning Cycle 5E Terhadap Hasil Belajar Peserta didik Kelas X SMA Negeri 1 Kajuara Kabupaten Bone - Wardah Sari; Sumiati Side; Muhammad Anwar (ChemEdu, 2020)
The research was a quasi-experimental that aimed to know the positive effect of using mind mapping method on learning cycle 5E models towards student achievement at class X Senior High School 1 Kajuara. The population in experiment was class X Senior High School 1 Kajuara Bone Regency are 9 Class with 320 peoples, the sample of this research consisted of two classes, namely class X1 as a experiment class with the number of students was 28 and class X4 as a control class with the number of students 30 peoples. The independent variable in this research was using mind mapping noted technique on learning cycle 5E models and without mind mapping noted technique on learning cycle 5E models, the dependent variable was learning achievement on subject matter Chemical Bond. Data which get form descriptive and inferential analysis. From analysis get the average value of experiment class is 71 with deviation standard is 9.35 while in control class the average is 65.30 with deviation standard is 10.14 and the percentage in class experiment is 57.14% while control class is 30%. The result of hypothesis analysis use t-test got tcalculate = 2.21 and significant level α = 0,05 with dk = 56 got ttable = 1,66. So that, tcalculated > ttable, so H1 accepted and H0 rejected. It means that mind mapping noted technique on learning cycle 5E model has effect toward student achievement class X Senior High School 1 Kajuara Bone Regency in chemical bond matter.